2006
DOI: 10.1111/j.1440-1746.2006.04485.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin of hepatocellular carcinoma: Role of stem cells

Abstract: The question of whether hepatocellular carcinoma (HCC) arises from the differentiation block of stem cells or dedifferentiation of mature cells remains controversial. Recently, researchers suggested that HCC may originate from the transdifferentiation of bone marrow cells. Interestingly, there are four levels of cells in the hepatic stem cell lineage: bone marrow cells, hepato-pancreas stem cells, oval cells and hepatocytes. Hematopoietic stem cells and the liver are known to have a close relationship in early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 95 publications
(178 reference statements)
4
38
0
Order By: Relevance
“…We thus found that the increase in liver size induced by exposure to DDC was also enhanced in these animals compared with that in control mice. Finally, WW45 Liv-cKO mice developed tumors with a mixed (HCC/CC) phenotype, with such tumors being thought to originate from transformed oval cells (13,14,16). These tumors are thus distinct from the HCC, originating from aberrant proliferation of hepatocytes, that was observed in the MST1/2 conditional knockout mice (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus found that the increase in liver size induced by exposure to DDC was also enhanced in these animals compared with that in control mice. Finally, WW45 Liv-cKO mice developed tumors with a mixed (HCC/CC) phenotype, with such tumors being thought to originate from transformed oval cells (13,14,16). These tumors are thus distinct from the HCC, originating from aberrant proliferation of hepatocytes, that was observed in the MST1/2 conditional knockout mice (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, some primary hepatomas exhibit an intermediate or combined (HCC/CC) phenotype and are thought to be derived from transformed progenitor (oval) cells or by dedifferentiation of mature cells (10)(11)(12)(13)(14)(15)(16). Oval cells are thought to be bipotential progenitor cells that can differentiate into either hepatocytes or ductal cholangiocytes but do so only if proliferation of hepatocytes is inhibited (17)(18)(19).…”
mentioning
confidence: 99%
“…Three levels of cells that can respond to liver tissue renewal or damage have been verified [8][9][10]. The first is mature liver cells, also called hepatocytes.…”
Section: Populations Of Liver Stem Cellsmentioning
confidence: 99%
“…Oval cells are the stem cells of liver (Bird et al, 2008;Strick-Marchand et al, 2008;Okabe et al, 2009;Shupe et al, 2009). Recently a great deal of research suggested a positive relationship between its proliferation and the incidence of hepaticarcinoma (Alison et al, 2005;Alison et al, 2006;Wu et al, 2006). Thy-1, as a marker protein of oval cells, has recently been suggested to play a role in potential liver cancer stem cells (Dahlke et al, 2003;Ceafalan et al, 2005;Masson et al, 2006;Xu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%